2012
DOI: 10.1016/j.ijcard.2010.12.089
|View full text |Cite
|
Sign up to set email alerts
|

Viral and bacterial patterns induce TLR-mediated sustained inflammation and calcification in aortic valve interstitial cells

Abstract: Exposure of aortic valve interstitial cells to viral and Gram-negative bacteria molecular patterns induces distinct and long-term TLR-mediated pro-inflammatory and pro-osteogenic responses that might be relevant to the pathogenesis of degenerative aortic stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 30 publications
6
60
1
Order By: Relevance
“…that observed in the early stages of atherosclerosis) [114]. In addition, in 2012 the group of Garcia-Rodrigues [115] investigated TLR-mediated inflammation and osteogenesis in interstitial human cells, isolated from stenotic and non-stenotic aortic valves and stimulated with viral and Gram-negative bacteria molecular patterns. TLR-expression and signaling were evaluated by several assays, including quantitative-PCR and flow cytometry, to Western blot analysis, ELISA, and cytokine arrays.…”
Section: Role Of Tlr-4 Pathway In Aneurysms (Sporadic Taa)?mentioning
confidence: 99%
See 2 more Smart Citations
“…that observed in the early stages of atherosclerosis) [114]. In addition, in 2012 the group of Garcia-Rodrigues [115] investigated TLR-mediated inflammation and osteogenesis in interstitial human cells, isolated from stenotic and non-stenotic aortic valves and stimulated with viral and Gram-negative bacteria molecular patterns. TLR-expression and signaling were evaluated by several assays, including quantitative-PCR and flow cytometry, to Western blot analysis, ELISA, and cytokine arrays.…”
Section: Role Of Tlr-4 Pathway In Aneurysms (Sporadic Taa)?mentioning
confidence: 99%
“…Moreover, they showed that TLR3 and TLR-4 agonists induced alkaline phosphatase expression and activity. Thus, they concluded that exposure of aortic valve interstitial cells to viral and Gramnegative bacteria molecular patterns induces distinct and long-term TLR-mediated pro-inflammatory and pro-osteogenic responses, likely relevant in the pathogenesis of degenerative aortic stenosis [115].…”
Section: Role Of Tlr-4 Pathway In Aneurysms (Sporadic Taa)?mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, proinflammatory mediators, such as tumor necrosis factor-α, have been shown to up-regulate the expression of osteogenic factor bone morphogenetic protein-2 (BMP-2) and early osteoblastic differentiation biomarker alkaline phosphatase (ALP) in AVICs (6, 7). We and others have observed that stimulation of either Toll-like receptor (TLR) 2 or TLR4 induces the osteogenic responses characterized by the expression of BMP-2 and ALP, among several other osteogenic biomarkers, in human AVICs (8)(9)(10)(11)(12), leading to the formation of calcification deposits in vitro (11)(12)(13). Moreover, bacteria associated with chronic periodontal infection and bacterial agents have been detected in diseased human aortic valves (14,15), and inoculation of rabbits with oral bacteria induces aortic valve lesions (16).…”
mentioning
confidence: 99%
“…Previous work demonstrated that TLR3 stimulation also activates NF-κB in human AVICs (41,42). However, we recently found that the TLR3-TRIF cascade activates noncanonical NF-κB in human AVICs, whereas LPS activates canonical NF-κB in this cell type (43).…”
Section: Disclosurementioning
confidence: 72%